Among Heroes A Marine Corps Rifle Company on Peleliu - Ainsworth, Jack R. (Marine Corps University Press (MCUP), 2011)
Few Americans know of the battle of Peleliu. It never received the iconic recognition of the other amphibious assaults in the Pacific during World War II such as Iwo Jima or Okinawa. At the time of the invasion in 1944, only a handful of journalists even covered the operation because it was expected to be a short action with a quick American victory. It became the bloodiest battle in Marine Corps history given the number of casualties compared to the number of troops involved. It lasted far longer than senior planners had estimated and the tenacious defense by the Japanese took a tremendous toll on the Marines' headlong assaults on their well-fortified positions.